FAKTOR-FAKTOR PENERAPAN INSTITUTIONAL REPOSITORY DI PUSAT PERPUSTAKAAN IAIN PONTIANAK - Asrika, Wiwit; sahid, Sahidi; Rahman, Miftah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
In this study, the establishment of the institutional repository at the IAIN Pontianak Library Center is discussed in detail. In the area of information technology, an institutional repository is a type of library development that makes it easy to manage, gather, preserve, and share material that might support learning and research activities. The goal of this study was to identify the internal and external variables that influence the institutional repository's implementation at the Pontianak IAIN Library Center. Descriptive study using a qualitative approach is the research methodology used. Observations, documentation, and conducting interviews are all used in the data collection process. The head of the library and members of the IT staff made up the study's informants. Data reduction, data visualization, and summary diagrams are some of the data analysis approaches employed. The findings indicated that open access, document digitalization, and webometrics were the internal implementation aspects of the IAIN Pontianak institutional repository. The two cooperating factors are: 1) Open access; 2) Document digitization; 3.) webometrics. The external factors consist of: 1) online publication of works; and 2) cooperation The results of this study show that internal factors that affect the implementation of institutional repositories IAIN Pontianak are derived from open access, document digitization, and webometics. While the external consists of the publication of scientific papers online and cooperation.